Anti-inflammatory effect of a novel formulation of coconut inflorescence sap against ox-LDL induced inflammatory responses in human peripheral blood mononuclear cells by modulating TLR-NF-κB signaling pathway. (13th October 2017) - Ratheesh, M.; Svenia, Jose P.; Asha, S.; Sandya, S.; Girishkumar, B.; Krishnakumar, I. M.
Abstract: Oxidized low density lipoprotein (ox LDL) induced inflammatory response was reported to play an important role in the pathogenesis of atherosclerosis. The purpose of this study was to explore the anti-inflammatory effect of a novel formulation of coconut inflorescence sap (CSP); COCOZEN™ against ox-LDL induced inflammatory responses in human peripheral blood mononuclear cells (hPBMCs). The hPBMCs were isolated from healthy human volunteers and cultured in collagen coated plates at 37 °C. The cells were grouped as Group I (Control), Group II (ox-LDL treated) and Group III (ox-LDL + CSP treated). Further analysis of inflammatory markers, reactive oxygen species, mRNA and protein expression levels indicated increased expressions of TLR-4, TNF-α, IL-6 and VCAM-1 in ox-LDL treated group along with the nuclear translocation of NF-κB. Other inflammatory markers such as LOX, PGE2, NO, total COX and lipid peroxidation level were also found to be significantly ( p  < .05) increased upon Ox-LDL treatment. The treatment with CSP on the other hand was found to down regulate and reverse the ox-LDL-induced alterations indicating its potential anti-inflammatory effect on hPBMCs via TLR-NF-κB signaling pathway.